Locating Tremor Source with Polarization and Semblance Methods During the 2014 Crisis Period of Raung Volcano - Vico Luthfi Ipmawan; Kirbani Sri Brotopuspito; Hetty Triastuty (Indonesian Journal on Geoscience, 2020)
DOI:10.17014/ijog.7.1.41-49Raung is a basaltic-andesitic volcano with strombolian-type eruptive activity located in East Java Province, Indonesia. The seismic activity of this volcano increased on 11th November 2014 which was dominated by tremors. Due to the difficulty to distinguish the onset of body waves of tremor waveform, polarization and semblance methods were proposed and applied to locate the tremor source. The tremors recorded during November to December 2014 were analyzed. The results showed that the back-azimuth values obtained by the polarization method were around N 288o - 324o E in accordance with the direction of Raung summit, while the incidence angle ranged around N 81o - 89.3o E. The semblance method was performed on 2 x 2 km area around the summit. The result of the tremor source showed the distribution of epicentre extending N52o E to the northeast direction about ±2.1 km away from the Raung summit.